The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/jph.12274
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Venturia inaequalis to Trifloxystrobin and Difenoconazole in Uruguay

Abstract: The sensitivity of Venturia inaequalis to trifloxystrobin and difenoconazole was studied in Uruguay. Populations of V. inaequalis were collected from apple orchards with different histories of trifloxystrobin use. Sensitivity of populations to trifloxystrobin was analysed using a method for testing spore germination published by FRAC, using a discriminatory concentration of 2.0 mg a.i./l. Resistance to trifloxystrobin was widespread in the region of commercial apple production with resistance detected in all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…Other authors found similar distributions of sensitivity to myclobutanil in baseline populations 1,24 . Some studies used one dose rather than a range in the sensitivity tests 22,28,29 . Using a single discriminatory dose is helpful where the sensitivity distribution is clearly bimodal, because the classification of an isolate is unchanged as long as the cut‐off is kept between the two modes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other authors found similar distributions of sensitivity to myclobutanil in baseline populations 1,24 . Some studies used one dose rather than a range in the sensitivity tests 22,28,29 . Using a single discriminatory dose is helpful where the sensitivity distribution is clearly bimodal, because the classification of an isolate is unchanged as long as the cut‐off is kept between the two modes.…”
Section: Discussionmentioning
confidence: 94%
“…worked with the diameters of single spore colonies, as in the present study. However, they and many other in vitro studies 6,23,27,28 used growth of the colony relative to the control (RG), whereas we used the actual mean growth at each concentration of chemical as response. We consider this preferable because dividing the growth by that of the control both introduces the error associated with the control into every measurement and loses a degree of freedom in the error estimate.…”
Section: Discussionmentioning
confidence: 99%
“…However, the repeated use of single-site chemical fungicide, such as demethylation inhibitor fungicide (DMIs), has rapidly led over time to the development of V. inaequalis strains with reduced sensitivity to triazoles fungicides (Köller et al, 1995; Gao et al, 2009; Xu et al, 2010; Villani et al, 2015). Besides, many cases of resistant strains of V. inaequalis have been recorded worldwide: in north and south America (Hildebrand et al, 1988; Köller et al, 1991, 1995; Braun and McRae, 1992; Carisse and Pelletier, 1994; Mondino et al, 2015), in Europa (Kunz et al, 1997; Gao et al, 2009; Xu et al, 2010) and in Asia (Shirane et al, 1996; Vijaya Palani and Lalithakumari, 1999). In organic farming, apple scab can be managed using sulfur or copper.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of dodine in spray programs is important since there is a low risk of resistance development by V. inaequalis. Furthermore, the new formulation of dodine is not associated with fruit russeting, an issue commonly observed after applications with previous formulations of the fungicide [12]. The limitation of the use of the systemic fungicides cyprodinil, dodine and difenoconazole is highly recommended because of the resistance developed by the pathogen [16].…”
Section: Discussionmentioning
confidence: 99%
“…Spray programs may include protectant fungicides with multisite activity, which affect primarily spore germination, such as dithianon (quinone class), captan (phthalimide class) and Bordeaux mixture (copper-based), or systemic fungicides, which are absorbed by the plant and affect fungal growth, such as dodine (guanidine class), difenoconazole (demethylation inhibitor group; DMIs), pyraclostrobin (quinone-outside inhibitors; QoIs) and the anilinopyrimidine cyprodinil [11]. However, among all fungicides used against apple scab, a complete loss of efficacy in practice has been observed only in the case of the QoIs [12][13][14]. A recent survey in major apple growing areas in Greece, including the area of the trial site, revealed for the first time the occurrence of V. inaequalis strains with differential multi-drug resistance to the fungicides pyraclostrobin, dodine, difenoconazole, boscalid and cyprodinil [15].…”
Section: Introductionmentioning
confidence: 99%